MITIGASI DAERAH RAWAN LONGSOR DI KABUPATEN LIMA PULUH KOTA, SUMATERA BARAT - Yona Febriania; Shofiyah Azizah; Teguh Widodo (Universitas Negeri Padang, 2020)
Lima Puluh Kota is one of the regency in West Sumatera Province that prone to Lima Puluh Kota is one of the regency in West Sumatera Province that prone to landslide, particularly when the rainfall intensity is high. Therefore, The availability of complete and accurate information in controlling land use in landslide prone areas in the development of an area becomes very important in minimizing the loss of life and losses, both physical, social and economic. This information must be disseminated to the community as an early warning system in disaster mitigation efforts. Identification of the characteristics of landslide prone areas requires a risk mapping of landslide prone areas in efforts to mitigate disasters can be done using Geographic Information Systems (GIS). The results in this study indicate the need to identify disaster risk in detail because basically, an area threatened by disaster does not necessarily mean that each community has the same level of disaster risk. Mapping can be done by clustering or by identifying each building in a vulnerable area based on the level of risk of landslides.